Rencana Anggaran Biaya dengan Metode BOW pada Pembangunan Ruang Kelas Baru Universitas Sunan Giri Surabaya - Mochamad Djaelani; Ella Anastasya Sinambela (Pusat Riset dan Inovasi Nasional, 2022)
The need for space to carry out human activities is increasing day by day. One of them is for teaching and learning activities that require better classrooms. With the growth in the number of students, the need for classrooms cannot be avoided. Classroom construction is a form of labor-intensive construction work. To start construction activities, start by budgeting construction costs. Cost budgeting is required so that the contractor can provide information to the client regarding the required costs. This study aims to determine the budget for building classrooms. The study used the BOW method. The BOW method is considered sufficient because it makes the building labor intensive. The research was conducted on an area of ​​5 x 7 meters. The results showed that to build a classroom on vacant land, Rp. 74.567.534. Contractors strengthen foundation work such as concrete work, wall work, and floor work. These three jobs use higher construction costs.